PENGARUH CAR, LDR, DAN EPS TERHADAP HARGA SAHAM (STUDI PADA BANK BUMN YANG LISTING DI BEI PERIODE 2012 – 2016) - Dian Fordian (Institut Informatika Dan Bisnis (IIB) Darmajaya, 2017)
This research aims to know and study the influence of variable EPS, CAR, and LDR against. The object of this research is the State-Owned bank listed in the 2012-2016 period BEI. The data used are secondary data in the form of annual data are taken from the annual reports of each bank i.e. bank BNI, independent, BTN, and BRI. The dependent variable is the price of the stock while the independent variable is CAR, LDR, and EPS. Data analysis using multiple regression equation regression estimation model using a Common Effect Model or Pooled Least Square (PLS). The results of this research show that there is a significant influence of the simultaneous independent variable that is used against the dependent variable. While partially only a positive and influential EPS variables significantly to the stock price, while variable CAR and LDR have no effect against the State-Owned bank share price listed at the IDX. Keywords: Stock Prices, CAR, EPS, LDR, Listed